Soehadi Prijonegoro: Dokter Jawa Pertama di Sragen - Lutfiana, Novisa Hayiq (Journal of Indonesian History, 2023)
Doctors play an important role in developing health services for the community, but the government's lack of attention to health makes the presence of doctors very minimal. The situation was getting worse, and there was a change in policy on ethical politics, which gave birth to native doctors who were placed in various regions so that they could spearhead the development of health services, including doctor Soehadi Prijonegoro. This study aims to discuss: (1) health conditions and the availability of health services in Surakarta, especially Sragen, at the beginning of the 20th century. (2) the background of Dr Soehadi Prijonegoro, and (3) the role of Doctor Soehadi Prijonegoro in developing health services in Sragen 1933-1978. This historical research uses historical research methods, which include heuristics, source criticism, interpretation and historiography. The results of this study indicate that health services in Sragen before 1933 were very limited and paid little attention. An epidemic and a shortage of health workers prompted the Regent of Sragen to work in Sragen. In 1933 Dr Soehadi Prijonegoro was sent to Sragen to serve the community. From 1933-1978, Dr Soehadi accompanied the development of health services in Sragen, which was indicated by establishing various health services in Sragen. The conclusion of this study is the presence of Dr Soehadi as the only doctor in Sragen for 30 years has made him responsible for the health sector for the people of Sragen. During his tenure, he has accompanied the development of health services in Sragen, which is growing rapidly.